Beyond ‘doing both’—framing carbon removal carefully - Markusson, Nils; von Rothkirch, Juanita; Dooley, Kate (Frontiers in Climate, 2026)
There is a common framing in communications about carbon dioxide removal (CDR) which amounts to saying ‘we need to do both’ CDR and emissions reductions, but without explaining further what this means or how to achieve it. This leaves the impression that such framing is empty and performative, doing little to counteract the risk of mitigation deterrence, i.e., that the pursuit of CDR undermines and delays emission reductions, which the framing is meant to address. This article substantiates and illustrates this claim, and develops recommendations for how to frame CDR more carefully. Such careful framing crucially involves indicating the relatively minor role CDR can play compared to emissions reductions on the path to net zero. Finally, we reflect on the barriers to and importance of these recommendations being taken up.